Karakteristik Fermentasi Kedelai yang Diperkaya Cu dengan Rhizopus oryzae: Characteristics Different of Cu Enriched Soybean with Rhizopus oryzae - Prasasti, H A; Toharmat, T; Prihantoro, Iwan (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
Copper (Cu) addition prevents deficiency and optimizes the enzyme system, metabolic system, and increases immunity. This study examines Rhizopus oryzae in soybean media with the addition of Cu and different fermentation times on fluctuations in soybean media fermentation. The study used a factorial completely randomized design with two factors with 4 replications. Factor A is Cu (0, 500, 1000, 1500, 2000 ppm), and factor B is the fermentation time (0, 1, 2, 3, 4 days). The variables observed were humidity, media shrinkage, dry matter (DM), organic matter (OM), ash, and pH. Data were analyzed using Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT) using SPSS 25. The results showed that fermented soybean media Rhizopus oryzae, Cu significantly (p<0.05) reduced media shrinkage, ash, and acidity levels, and did not affect BK, and BO. Based on the fermentation time, it significantly (p<0.05) reduced media shrinkage, BK and BO, did not affect ash, and increased acidity levels. The conclusion of the study is that Cu has influence on effectiveness of Rhizopus oryzae on soybean media.